2019
DOI: 10.1029/2018jd030088
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Effect on the Cloud Phase of Low‐Level Clouds Over the Arctic

Abstract: Three years of nighttime Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation data was used in synergy with CloudSat measurements to quantify how strongly aerosol type and aerosol load affect the cloud phase in low‐level clouds over the Arctic. Supercooled liquid layers were present in the majority of observed low‐level clouds (0.75 ≤ z ≤ 3.5 km) between −10 and −25 °C. Furthermore, based on the subset (6%) of data with high quality assurance for aerosol typing, ice formation is more common in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…It is possible that Antarctic clouds glaciate at lower temperature than other clouds because Antarctic clouds are in contact with lower concentrations of aerosols that may serve as potential ice nuclei and facilitate phase transitions. Coopman et al (2018) studied the phase transition of Arctic clouds for different regimes of pollution from fossil fuel combustion and retrieved a glaciation temperature of about −20 • C; the presence of pollution increases the glaciation temperature up to 4 • C. Similarly, Filioglou et al (2019) have shown from CALIPSO and CloudSat measurements that high aerosol loadings increase the glaciation temperature by 10 • C in presence of dust and continental aerosols in the Arctic. We suggest that larger liquid cloud droplets are associated with higher glaciation temperatures because they aid secondary ice nucleation (Rosenfeld et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that Antarctic clouds glaciate at lower temperature than other clouds because Antarctic clouds are in contact with lower concentrations of aerosols that may serve as potential ice nuclei and facilitate phase transitions. Coopman et al (2018) studied the phase transition of Arctic clouds for different regimes of pollution from fossil fuel combustion and retrieved a glaciation temperature of about −20 • C; the presence of pollution increases the glaciation temperature up to 4 • C. Similarly, Filioglou et al (2019) have shown from CALIPSO and CloudSat measurements that high aerosol loadings increase the glaciation temperature by 10 • C in presence of dust and continental aerosols in the Arctic. We suggest that larger liquid cloud droplets are associated with higher glaciation temperatures because they aid secondary ice nucleation (Rosenfeld et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…where r n is the radius of the insoluble portion of the droplet, k is Boltzmann's constant and T is temperature. The pre-exponential factor (kinetic coefficient) is 10 26 (cm −2 )r 2 n (Fletcher, 1962). Here, the case-dependent activation energy F act is set to zero (Khvorostyanov and Curry, 2000).…”
Section: Appendix A: Immersion Freezingmentioning
confidence: 99%
“…Biomass burning was suggested as the possible origin of this phenomenon, as it strongly influenced the aerosol composition during the season, injecting biological material, soil dust, and 10.1029/2020GL088030 ash particles into the atmosphere. Filioglou et al (2019) also addressed the effect of aerosol type (classified as marine, continental, dust, and elevated smoke) and aerosol load on the cloud phase (water, mixed-phase, and ice) of Arctic low-level clouds. Although they introduced a quantitative parameter, aerosol optical depth, to estimate the role of the aerosol load on freezing, their discussion was limited to two categories: high and low aerosol optical depths.…”
Section: Comparison With Previous Studies On Icf Behaviorsmentioning
confidence: 99%